Synthetic, kinetic and electrochemical aspects of ferrocene- and ruthenocene-containing titanium(IV) complexes with biomedical applications - Erasmus, Elizabeth (University of the Free State, 2005)
In this study, ruthenocene-containing β-diketones, ruthenocene-, cobalticenium- and/or ferrocene- containing enaminones and ruthenocenyl and/or ferrocenyl containing titanium(IV) complexes were synthesised. Forty seven of these compounds were previously unknown. The keto-enol isomerization kinetics of the β-diketones RcCOCH2COR with R = C10F21, CF3, C6F5, C10H21, CH3, Rc and Fc have been studied by 1H NMR spectroscopy in CD3CN. The influence of the solvent on this equilibrium has also been investigated utilising CD2Cl2 and CDCl3 as different solvents. The substitution reactions of the monodentate ferrocene-containing alkoxy groups of [Ti(O(CH2)nFc)2(RcCOCHCOCH3)2] {n = 1, 2, 3} with HO(CH2)nFc {n = 2, 3, 4} and the substitution of the bi-dentate β-diketonato ligand of [Ti(O(CH2)4Fc)2(RcCOCHCOR)2] {R=CH3, CF3} with RcCOCH2COR {R = CH3, CF3} is reported. Both revealed large positive entropy values, which suggest a dissociative substitution mechanism. Electrochemical studies were conducted in dichloromethane in the presence of [NBu4][B(C6F5)4] as uncoordinating supporting electrolyte. All ruthenocene-containing complexes exhibited chemically and electrochemically irreversible behaviour for the Ru3+/Ru2+ and Ti4+/Ti3+ couples. In contrast, the Fc/Fc+ couples were mostly found to be electrochemically quasi-reversible and chemically reversible. It was found that E01, Epa and Epc are dependent on either the alkyl chain length of the ferrocene-containing alkoxy group or the group electronegativity of the R-group of the β-diketonato ligand in all complexes. Cytotoxic studies revealed that complexes [(C5H5)2Ti(RcCOCHCOR)]+ClO4, TiCl2(RcCOCHCOR)2 and Ti(O(CH2)4Fc)2(RcCOCHCOR)2, (R = C10F21, CF3, C6F5 or Fc), which contains more than one antineoplastic moiety, were the most effective in killing CoLo and HeLa cancer cell lines. These results are probably due to a synergistic effect between different fragments possessing anti-cancer activity in the same molecule. Phase change studies of the complexes containing the long alkyl chains (R = C10H21, C10F21) and the crystal structure of [(C5H5)2Ti(RcCOCHCOCH3)]+ClO4 are also reported.

In hierdie studie is ferroseenbevattende alkohole, rutinoseenbevattende β-diketone, rutinoseen-, kobaltisenium- en/of ferroseenbevattende enaminone en rutinoseen- en/of ferroseenbevattende titanium(IV) komplekse gesintetiseer. Sewe-en-veertig van hierdie verbindings, was tot nog toe totaal onbekend. Die keto-enol isomerisasie kinetika van die β-diketone RcCOCH2COR met R = C10F21, CF3, C6F5, C10H21, CH3, Rc en Fc is met behulp van 1H KMR spektroskopie in CD3CN bestudeer. ‘n Oplosmiddel invloed op hierdie ewewig is ook met behulp van CD2Cl3 en CDCl3 as oplosmiddels nagevors. Die subsitutusie reaksies van die monodentate ferroseenbevattende alkoksiegroepe vanaf [Ti(O(CH2)nFc)2(RcCOCHCOCH3)2] {n = 1, 2, 3} met HO(CH2)nFc {n = 2, 3, 4}asook die bidentate β-diketonato ligande van [Ti(O(CH2)4Fc)2(RcCOCHCOR)2] {R = CH3, CF3} met RcCOCH2COR {R = CH3, CF3}is gerapporteer. In beide gevalle is groot positiewe entropie waardes gekry. Hierdie resultaat impliseer ‘n dissosiatiewe substitusie meganisme. Elektrochemiese studies is uitgevoer in dichlorometaan in die teenwoordigheid van [NBu4][B(C6F5)4] as nie-koordinerende ondersteuningselektroliet. Alle rutinoseen- en titaniumbevattende komplekse vertoon chemiese en elektrochemiese onomkeerbaarheid vir die Ru2+/Ru3+ en Ti4+/Ti3+ koppels. Daarteenoor het die meeste van die Fc/Fc+ koppels elektrochemiese quasi-omkeerbare en chemiese omkeerbare gedrag getoon. Dit is bevind dat E01, Epa en Epc afhanklik is van óf die alkiel ketting lengte van die ferroseenbevattende alkoksie groep óf die groep elektronegatiwiteit van die R-groep van die β-diketonato ligand in alle komplekse. Sitotoksiese studies het getoon dat komplekse soos [(C5H5)2Ti(RcCOCHCOR)]+ClO4, TiCl2(RcCOCHCOR)2 en Ti(O(CH2)4Fc)2(RcCOCHCOR)2, (waar R = C10F21, CF3, C6F5 of Fc) wat meer as een antineoplastiese fragment bevat, meer effektief CoLo en HeLa kankersellyne dood. Hierdie resultaat is moontlik toe te skryf aan ‘n sinergistiese effek wat tussen die verskillende kankerbestrydende molekulere fragmente bestaan. Fase eienskappe van die komplekse wat lang kettings bevat (R = C10H21, C10F21) is ook bestudeer en die kristal struktuur van (C5H5)2Ti(RcCOCHCOCH3)]+ClO4 is gerapporteer.
Thesis (Ph.D. (Chemistry))--University of the Free State, 2005
Keywords: Titanium; Ruthenocene; Ferrocene; β-diketones; Electrochemistry; Cytotoxicity; Titanium -- Synthesis; Organometallic compounds